Modelagem e determinação do estado crítico de consolidação a partir da relação massa e volume em solos canavieiros - Silva, Reginaldo Barboza da [UNESP]; Iori, Piero; Silva, Francisca Alcivania de Melo [UNESP]; Lanças, Kléber Pereira [UNESP]; Dias Júnior, Moacir de Souza (My University, 2010)
The objectives of this research was to suggest equations, to estimate the bulk density (ρσp) and total porosity (nσp), on the precompression stress (σp), proposing them as indicators for the evaluation of the quality and the critical consolidation state of farmland. The physical characteristics were obtained by uniaxial precompression tests of undisturbed samples of an Alfisol after being subject to the following states of consistency: toughness, friability and plasticity. The results allowed estimating the ρσp and nσp which the soil can reach without having its structure degraded. The equations were shown to be powerful tools in assessing the soil bearing capacity and the maximum mass-volume ratio that may reach the ground.

O trabalho teve por objetivo sugerir equações, as quais permitam estimar a densidade do solo (ρσp) e o volume total de poros (nσp), ambos referentes à pressão de preconsolidação (σp), propondo-os como indicadores físicos na avaliação da qualidade e do estado crítico de consolidação dos solos agrícolas. Os índices físicos foram obtidos por meio de ensaios de consolidação uniaxial de amostras indeformadas de um Nitossolo Vermelho, depois de submetidas aos seguintes estados de consistência: tenacidade, friabilidade e plasticidade. Os resultados permitiram estimar a ρσp e a nσp que o solo pode atingir para que o mesmo não tenha a sua estrutura degradada. As equações mostraram-se ferramentas poderosas na avaliação da capacidade de suporte de carga dos solos podendo estimar a máxima relação de massa/volume que o solo pode atingir.
Modeling and determination of critical state of consolidation from mass-volume ratio in farmland
Keywords: Compressibility; Preconsolidation pressure; Spatial variability; Sugar cane; Cana-de-açúcar; Compressibilidade; Pressão de preconsolidação; Variabilidade espacial